A Programmable Phase Shifter for Sinusoidal Signals - Muhammad Taher Abuelma'atti; Uthman Baroudi (Active and Passive Electronic Components)
A simple current(voltage)-controlled phase shifter is presented. The circuit uses a small number of active and passive Components. The feasibility of obtaining a temperature-insensitive phase shifter is explored. Experimental and simulation results are included.